Measurement of the Hematocrit Using a Paper-Based Microfluidic Device. - Berry, Samuel. (Tufts Archival Research Center, 2016)
The detection and quantification of blood cells provide critical information about a patient’s health status. A number of sophisticated instruments, such as hematology analyzers, have been developed to perform these measurements, but limited-resource settings are often lacking the infrastructure required to purchase, operate, and maintain instrumentation. To address the practical difficulties of limited-resource settings, paper-based microfluidic devices have matured as an analytical platform that is capable of performing diagnostic assays in order to provide reliable clinical information. To date, the focus on the use of these tools has been limited to immunoassays, clinical chemistry, and electrochemistry. However, we investigated the use of a paper platform to allow, rather than impede, the flow of cells through paper in order to establish methods for cell assays in paper-based devices. As a proof-of-concept, we developed a paper-based tool for the determination of the hematocrit—the ratio of red blood cell (RBC) volume to total volume of whole blood. We investigated the effects the physical properties of paper had on the device for promoting the transport of RBCs in plasma in paper. The ideal conditions for the fabrication of our device were determined based on our observation of a linear relationship (R2=0.991) between the lateral distance RBCs traveled and the hematocrit percentage. Our work provides information necessary for overcoming the challenges of developing cell assays in paper-based devices.